New labels for old problems: grammar in communicative language teaching (2003)
Communicative language teaching has long been controversial due to its lack of explicit grammar instruction. Focus on form instruction (Long, 1991), however, puts communication as the centerpiece of instruction, but addresses form on a need-toknow- basis; thus, focus on form instruction claims to balance communication and grammar. Moreover, the concept of uptake (Lyster and Ranta, 1997; Ellis, Basturkmen, and Loewen, 2001), or the process by which learners respond to correction initiated by teachers and/or other learners, has been used to demonstrate that focus on form instruction, and thus by extension, CLT, gives sufficient attention to grammar. However, in this article, I will show that the concept of uptake is problematic, and demonstrate that focus on form instruction does not offer a feasible way of addressing grammar in EFL classrooms. Yet, before showing the technique’s inadequacy, I will highlight selected aspects of focus on form instruction and uptake research. Key Words: English-Grammar-Teaching-Evaluation, Second Language Acquisition- Teaching, Grammar Instruction. La enseñanza comunicativa del lenguaje ha sido muy controversial debido no sólo a la carencia explícita de la enseñanza de la gramática, sino también a la carencia tangible para evaluar si los estudiantes han adquirido o no ciertas formas gramaticales. El enfoque de la forma (Long, l991), sin embargo, ubica la comunicación como pieza principal de enseñanza, pero a la vez enfatiza en la enseñanza de la forma como parte importante que todo estudiante necesita saber. Algunos autores han señalado la importancia de tener un balance entre la comunicación y la enseñanza explícita de la gramática. Esto se debe en gran parte, al concepto de ‘uptake’ que ha sido usado para demostrar que el enfoque en la enseñanza de la forma y, por extensión el enfoque en la enseñanza comunicativa del lenguaje, facilitan la atención a la gramática. Sin embargo, el concepto de ‘uptake’ es teórica y prácticamente problemático y demuestra que el enfoque de la enseñanza en la forma no es un camino viable para enseñar gramática en salones donde el inglés se enseña como idioma extranjero. Mi propósito en este artículo es: (1) Resumir las investigaciones concernientes a la enseñanza de la forma y ‘uptake’; (2) Debatir que ‘uptake’ y la enseñanza en la forma no son elementos suficientes para aprender inglés como idioma extranjero ya que es muy difícil prestar atención a la gramática. Palabras claves: Inglés-Gramática-Enseñanza-Evaluación, Adquisición de una segunda lengua-Enseñanza, Gramática-Instrucción